CatSper mediates not only chemotactic behavior but also the motility of ascidian sperm - Kijima, Taiga; Kurokawa, Daisuke; Sasakura, Yasunori; Ogasawara, Michio; Aratake, Satoe; Yoshida, Kaoru; Yoshida, Manabu (Frontiers in Cell and Developmental Biology, 2023)
Introduction: sperm motility, including chemotactic behavior, is regulated by changes in intracellular Ca 2+ concentration, and the sperm-specific Ca 2+ channel CatSper has been shown to play an important role in the regulation of intracellular Ca 2+ . In particular, in mammals, CatSper is the only functional Ca 2+ channel in the sperm, and mice that lack the genes that make up the pore region of the Ca 2+ channel are infertile due to the inhibition of sperm hyperactivation. CatSper is also thought to be involved in sea urchin chemotaxis. In contrast, in the ascidian Ciona intestinalis, SAAF, a sperm attractant, interacts with Ca 2+ /ATPase, a Ca 2+ pump. Although the existence of Catsper genes has been reported, it is not clear whether CatSper is a functional Ca 2+ channel in sperm. Results: we showed that CatSper is present in the sperm flagella of C. intestinalis as in mammalian species, although a small level of gene expression was found in other tissues. The